Impact of Orthodontic Treatment on Speech and Phonetics. A Cross-Sectional Study - Faryal Ali Syed, Ayesha Yasir, Samina Qadir, Ahmad Shamim Qureshi, Beenish Elahee Rizvi, Junaid Tariq (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Orthodontic treatment aims to correct malocclusion and improve aesthetics and oral function; however, alterations in intra-oral anatomy during treatment may temporarily affect speech and phonetics. Understanding these effects is important for improving patient comfort and communication confidence. Objective: To evaluate the impact of different orthodontic appliances on speech articulation, phonetic performance, and patient-perceived speech difficulty. Methods: A cross-sectional study was conducted in the Department of Orthodontics, Baqai Dental College, Karachi, Pakistan, from April 2022 to July 2023. A total of 130 patients aged 15–30 years receiving fixed labial, lingual, or removable orthodontic treatment were assessed. Speech recordings were obtained at three intervals before appliance placement, one week after, and one month after using a standardized list of phonemes (/s/, /z/, /ʃ/, /ʒ/, /t/, /d/). Auditory perceptual analysis and a self-administered questionnaire evaluated phonetic distortions and subjective difficulty. Data were analyzed with SPSS v26 using χ² and repeated-measures ANOVA tests. Results: Speech disturbances were most frequent during the first week, particularly in lingual appliance users (70%), followed by fixed labial (42%) and removable (33%) groups (p < 0.05). Sibilant sounds were most affected, with temporary lisping noted in 44.6% of participants. Mean self-perceived difficulty decreased significantly by the first month, indicating rapid phonetic adaptation. Conclusion: Orthodontic treatment may cause short-term speech and phonetic disturbances, especially with lingual appliances, but these effects resolve within four weeks as patients adapt. Early counseling and speech-adaptation guidance can enhance patient confidence and compliance during therapy. Keywords: Orthodontics, Speech Articulation, Phonetics, Lingual Braces, Speech Adaptation